A Concise, Catalyst-Free Synthesis of Davis’ Oxaziridines using Sodium Hypochlorite - Kitagawa, Saori; Mori, Hiromitsu; Odagiri, Tatsuya; Suzuki, Katsuya; Kikkawa, You; Osugi, Rie; Takizawa, Shinobu; Kimura, Yoshikazu; Kirihara, Masayuki (SynOpen, 2019)
N-Sulfonyloxaziridines (Davis’ oxaziridines) can be synthesized by reacting the corresponding N-sulfonylimines with aqueous sodium hypochlorite in acetonitrile without any catalyst. The pH of the aqueous sodium hypochlorite is crucial to obtain the product in high yield. Optimized conditions are presented that allow synthetically useful Davis’ oxaziridines to be easily obtained in up to 90% yields from the corresponding imines by using inexpensive, stable, environmentally friendly sodium hypochlorite pentahydrate crystals as the oxidant, with high reproducibility.
Keywords: oxaziridine; Davis’ oxaziridine; sodium hypochlorite; sodium hypochlorite pentahydrate; N-sulfonylimine; oxidation